2006
DOI: 10.1002/elps.200500583
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced binding and conformational selectivity in affinity capillary electrophoresis using a water‐soluble resorcin[4]arene as intrinsic buffer and electrokinetic host

Abstract: Affinity capillary electrophoresis (ACE) is a widely used technique for quantifying non-covalent molecular interactions that is dependent on the specific buffer conditions selected. In this study, dynamic 1:1 host-guest inclusion complexation involving a charged resorcin[4]arene with a group of neutral corticosteroids was examined by ACE, where the macrocycle serves as both an intrinsic buffer and electrokinetic host. It was determined that over a 200% enhancement in the apparent binding constant (KB) was real… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
(39 reference statements)
0
5
0
Order By: Relevance
“…CE is increasingly being recognized as a versatile biophysical tool for characterizing biomolecular interactions in free solution, ranging from high affinity protein-DNA interactions [1,2] to weaker host-guest inclusion complexation [3,4]. There is considerable interest in understanding the dynamics of folding in wild-type and recombinant protein due to its importance in determining its conformational state, thermodynamic stability, and overall biological activity.…”
Section: Introductionmentioning
confidence: 99%
“…CE is increasingly being recognized as a versatile biophysical tool for characterizing biomolecular interactions in free solution, ranging from high affinity protein-DNA interactions [1,2] to weaker host-guest inclusion complexation [3,4]. There is considerable interest in understanding the dynamics of folding in wild-type and recombinant protein due to its importance in determining its conformational state, thermodynamic stability, and overall biological activity.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, RSM in the form of a Box-Behnken design was implemented in flow-through PFACE (FTPFACE) ACE has been shown to be a versatile microanalytical technique to estimate affinity constants, and has emerged as a useful and sensitive method for studying bimolecular noncovalent interactions and for determining binding and dissociation constants of formed complexes. The first reports detailing the use of ACE to measure affinity parameters between biological species were published in the early 1990s [3][4][5][6][7]. Since these informative studies, a multitude of other interactions including protein-ligand, peptide-peptide, proteinpeptide, protein-antibody, polymer-peptide, and antibodyantigen have been examined successfully using ACE .…”
Section: Use Of Chemometric Methodology In Optimizing Conditions For mentioning
confidence: 99%
“…The first reports detailing the use of ACE to measure affinity parameters between biological species were published in the early 1990s [3][4][5][6][7]. Since these informative studies, a multitude of other interactions including protein-ligand, peptide-peptide, proteinpeptide, protein-antibody, polymer-peptide, and antibodyantigen have been examined successfully using ACE .…”
Section: Introductionmentioning
confidence: 99%
“…The analysis speed of the CE approach will, – in contrast to gel methods – in some cases make it possible to analyze quite weak interactions in preincubated samples by using very fast separations 66–68. Affinity CE is generally well suited for the study of weakly interacting systems as has been shown in many cases for small analytes 69–75. Also, frontal analysis by CE is feasible for weak binding interactions as have been especially exploited in drug–ligand interaction studies 76.…”
Section: Typical Applicationsmentioning
confidence: 99%
“…In its lifetime a substantial number of papers and reviews dealing with affinity interactions in electrophoretic techniques have been published in Electrophoresis (Table 1). More than 125 papers 18, 38, 46, 47, 49–53, 69–71, 93, 101, 110, 118, 129–238 with the word affinity in the title and dealing with some aspect of affinity electrophoresis have been published in the journal since 1989, the year it started being indexed in PubMed. Prior to that, i.e.…”
Section: Affinity Electrophoresis and Electrophoresismentioning
confidence: 99%